The Psychometric Properties of the Measure of Adolescent Relationship Harassment and Abuse (MARSHA) With a Nationally Representative Sample of U.S. Youth - Rothman, Emily F. (Journal of interpersonal violence, 2022)
This article describes a new instrument that assesses adolescent dating abuse (ADA) victimization and perpetration. The Measure of Adolescent Relationship Harassment and Abuse (MARSHA) is a comprehensive instrument that includes items on physical, sexual, and psychological ADA, as well as cyber dating abuse, social control, and invasion of privacy. Data for this study came from a population-based, nationally representative sample of adolescents ages 11 to 21 years old (N = 1,257). Exploratory factor analysis was conducted for the victimization and perpetration versions of the MARSHA, and convergent and divergent validity were assessed using the Conflict in Adolescent Dating Relationships Inventory (CADRI) and the juvenile victimization questionnaire (JVQ), respectively. Results suggest that the MARSHA has good reliability and validity, and that each subscale had good internal consistency. The authors propose that the MARSHA may be a strong alternative to the CADRI or the conflict tactics scale (CTS) because it reflects contemporary forms of abuse, such as online harassment and pressure to send nude selfies, and the nonconsensual dissemination of sexually explicit images.